High-density low-expansion multiphase honeycomb ceramic and preparation method thereof
By adding pre-sintered composite additives to honeycomb ceramics, the problem of reduced thermal shock and mechanical properties of ceramics in high-temperature environments is solved, and complex-phase honeycomb ceramics with high density and low expansion coefficient are realized, improving the overall performance of ceramics.
Patent Information
- Application Number
- CN202411460426.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-21
AI Technical Summary
Existing honeycomb ceramics are prone to thermal shock problems in high temperature environments, and high sintering temperature will lead to a decrease in the mechanical properties of the ceramics, making it difficult to achieve high density and low expansion coefficients at the same time.
By adding a pre -fired composite additive to ceramic raw materials, including mixture of oxide and aluminate, pre -sintering and grinding are performed. Combined with the appropriate sintering temperature control, it is made of high -expanded complex honeycomb ceramics.
The high density and low -thermal expansion coefficient of ceramics are achieved, and at the same time avoid cracking, reduce the sintering temperature, and improve the compressive strength and comprehensive performance of ceramics.
Smart Images

Figure CN119330743A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of honeycomb ceramics, and in particular to a high-density and low-expansion composite honeycomb ceramic and a preparation method thereof. Background Art
[0002] Regenerative Thermal Oxidizer (RTO) is a device used to treat and purify industrial waste gas. It decomposes organic pollutants (such as volatile organic compounds (VOCs)) and other harmful gases through high-temperature oxidation to achieve the purpose of purifying emissions. RTO uses heat storage materials (such as honeycomb ceramics) to recover heat from exhaust gas. Honeycomb ceramics have high heat capacity, excellent thermal conductivity and large surface area, which enables them to quickly absorb, store and release heat. In addition, the channel design of the honeycomb structure reduces the resistance to gas flow and improves the heat transfer efficiency. At the same time, the chemical stability and high temperature resistance of the material itself also ensure its long-term stability and durability in high temperature environments, thereby improving thermal efficiency and reducing operating costs. However, the operating temperature of honeycomb ceramics oscillates back and forth between 25°C and 850°C. It is stacked layer by layer in the RTO equipment, and the ceramic wall thickness is very small, which poses a challenge to the performance of the ceramics.
[0003] Patent CN101798212B discloses a method for preparing a dense alumina ceramic product. First, aluminum titanate ceramics are synthesized, made into powder, then injection molded, and finally sintered. The weight percentage of the synthetic raw materials of aluminum titanate ceramics is: 37.18-53.1% aluminum oxide, 32.82-46.9% titanium dioxide and 0-30% additives; wherein the weight percentage of the additives is: 0-30% mullite, 0-30% magnesia aluminum spinel, 0-40% cordierite and 0-100% basic magnesium carbonate.
[0004] Patent application CN112723903A discloses an aluminum titanate-mullite composite ceramic and a preparation method thereof, a porous medium burner and a ceramic filter, which belongs to the field of ceramic technology. The aluminum titanate-mullite composite ceramic includes an aluminum titanate crystal phase and a mullite crystal phase in a mass ratio of 6 to 7:3 to 4; the stabilizing component of the aluminum titanate-mullite composite ceramic is selected from at least one of magnesium oxide, strontium oxide, silicon dioxide, ferric oxide, cerium oxide, lanthanum oxide and yttrium oxide.
[0005] Patent CN108017387B discloses an aluminum titanate-mullite-corundum sagger and its preparation method and application, which relate to the field of refractory materials technology. The aluminum titanate-mullite-corundum sagger provided by the scheme mainly uses aluminum titanate, mullite of a specific particle size, corundum powder of a specific particle size, titanium dioxide, alumina, magnesium oxide powder and yellow dextrin as raw materials. The sintering temperature of the scheme is too high, which is above 1500 degrees Celsius.
[0006] It can be seen from the above that aluminum titanate can improve the thermal shock resistance of ceramics, and the problem of reduced mechanical properties caused by high-temperature decomposition of aluminum titanate can also be solved by adding stabilizers such as yttrium oxide, magnesium oxide, ferric oxide, and cerium oxide. For the composite ceramics of the cordierite-mullite-corundum system, the amount of aluminum titanate and stabilizer added should not be too much, and the ceramic sintering temperature should not be too high (cordierite is prone to decomposition at temperatures greater than 1400°C), which will result in the stabilizer having no significant effect on aluminum titanate. Summary of the invention
[0007] The present invention aims to provide a high-density and low-expansion composite honeycomb ceramic and a preparation method thereof. The prepared composite honeycomb ceramic has both high density and low expansion coefficient.
[0008] In order to achieve the above object, the technical solution adopted by the present invention is:
[0009] A method for preparing a high-density, low-expansion composite honeycomb ceramic, wherein a pre-sintered composite additive is added to a mixed ceramic raw material, the pre-sintered composite additive is 5-9wt% of the weight of the mixed ceramic raw material, and the pre-sintered composite additive is prepared by mixing yttrium oxide and aluminum titanate in a mass ratio of 1:5-7, and pre-sintering and grinding at 1350-1600°C.
[0010] The invention adds a pre-sintered composite additive into the mixed ceramic raw material, so that the prepared multi-phase honeycomb ceramic has high density and low expansion coefficient, and at the same time avoids cracking and reduces the sintering temperature.
[0011] The present invention improves the density of ceramics by using yttrium oxide, reduces the thermal expansion coefficient of ceramics by using aluminum titanate, and improves the problem of decreased mechanical properties caused by aluminum titanate by pre-sintering composite addition of yttrium oxide + aluminum titanate.
[0012] According to the embodiments of the present invention, the present invention can be further optimized. The following is the technical solution formed after optimization:
[0013] In one preferred embodiment, the pre-sintering temperature of the pre-sintered composite additive is 1500-1600°C.
[0014] This pre-sintering temperature range has a lower thermal expansion coefficient and higher compressive strength.
[0015] In one preferred embodiment, the pre-sintering time of the pre-sintered composite additive is 1 to 3 hours.
[0016] In one of the preferred embodiments, 3-5 wt% of yttrium oxide is also added to the mixed ceramic raw material.
[0017] By adding yttrium oxide, the densification of ceramics can be further promoted and the mechanical properties of ceramics can be improved.
[0018] In one of the preferred embodiments, the sintering temperature of the high-density and low-expansion composite honeycomb ceramic is 1150°C-1400°C.
[0019] The present invention reduces the sintering temperature of the composite honeycomb ceramic by adding a pre-sintering composite additive into the mixed ceramic raw material.
[0020] In one of the preferred embodiments, the sintering temperature of the high-density and low-expansion composite honeycomb ceramic is 1150°C-1350°C.
[0021] In one preferred embodiment, the mixed ceramic raw material is a cordierite-mullite-corundum composite honeycomb ceramic raw material; preferably, the mixed ceramic raw material includes the following raw materials in parts by weight: 40-60 parts of bauxite powder with an aluminum oxide content >80%, 2-6 parts of cordierite powder, 1-4 parts of Suzhou kaolin, 0.5-1.5 parts of pyrope powder, 20-35 parts of mullite powder, 2-4 parts of potassium feldspar, 4-9 parts of raw talc, 2-5wt‰ of dispersant with a total powder mass, and 0.5-2wt‰ of grinding aid with a total powder mass.
[0022] The present invention is particularly suitable for cordierite-mullite-corundum composite honeycomb ceramics. Composite honeycomb ceramics usually have good comprehensive properties, wherein cordierite provides good thermal shock resistance for the ceramics; mullite is resistant to high temperatures and can effectively improve the mechanical properties of the ceramics; and the corundum phase can improve the thermodynamic properties of the ceramics.
[0023] In one preferred embodiment, the method for preparing the high-density and low-expansion composite honeycomb ceramic comprises the following steps:
[0024] (1) Weighing each raw material by weight and ball-milling to obtain a mixed material;
[0025] (2) adding cellulose, a lubricant, a plasticizer and water to the mixture and kneading to obtain a kneaded mud segment;
[0026] (3) refining the kneaded mud segment to obtain a refined mud segment;
[0027] (4) using a mold to press the refined mud segment into a desired product to obtain a wet blank;
[0028] (5) drying the wet blank to obtain a dry blank;
[0029] (6) cutting the two ends of the dry blank to obtain a cut dry blank;
[0030] (7) The cut dry blank is fired to obtain a finished ceramic product.
[0031] Preferably, in step (1), the ball milling is performed at a speed of 10-40 revolutions per minute for 6-10 hours.
[0032] Preferably, step (2) is performed by kneading using a kneading machine, the kneading speed is 20-40 revolutions per minute, and the kneading time is 20 minutes.
[0033] Preferably, in step (2), the cellulose is HPMC, the viscosity is 50,000 to 150,000, and the added mass is 1-4% of the mass of the mixture. The lubricant is palm oil, the added mass is 1-3% of the mass of the mixture, and the addition temperature is 26 to 30 degrees. The plasticizer is polyethylene oxide, preferably, the molecular weight of polyethylene oxide is 1 million to 8 million, and further preferably, the added mass of the plasticizer is 3-10‰ of the mass of the mixture. The amount of water added is 10-20% of the mass of the mixture.
[0034] Preferably, in step (3), a vacuum mud kneader is used for refining, and the vacuum degree of refining is 0.06-0.09.
[0035] Preferably, the cutting size in step (6) is 1-1.20 times the length of the finished product.
[0036] Preferably, the firing temperature in step (7) is 1150°C-1400°C.
[0037] Preferably, the grinding aid is one or more of stearic acid, ethylene glycol, and propylene glycol. The dispersant is one or more of sodium polyacrylate, sodium hexametaphosphate, and triethanolamine.
[0038] The invention also discloses a high-density, low-expansion composite honeycomb ceramic prepared according to the preparation method.
[0039] The invention also discloses a high-density, low-expansion composite honeycomb ceramic, with a thermal expansion coefficient of less than 4.9×E-6 and a compressive strength of more than 58 MPa.
[0040] Compared with the prior art, the present invention has the following beneficial effects:
[0041] (1) The pre-sintering system effectively inhibits the decomposition of aluminum titanate and ensures that the ceramics are sintered at a lower temperature.
[0042] (2) The honeycomb ceramic product prepared by the present invention has the characteristics of high density and low thermal expansion. Among the additives, yttrium oxide can be pinned at the grain boundary to inhibit abnormal growth of grains, and aluminum titanate can reduce the thermal expansion coefficient. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 The present invention explores the phase composition of ceramics doped with 0-4% yttrium oxide in the experiment.
[0044] Figure 2 The present invention explores the phase composition of ceramics doped with 5-9% yttrium oxide in the experiment. DETAILED DESCRIPTION
[0045] The present invention will be described in detail below in conjunction with the embodiments. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.
[0046] 1. Effect of yttrium oxide on the properties of composite ceramics
[0047] Ceramic samples were prepared according to the above method, and the true density, water absorption, sintering line shrinkage, thermal expansion coefficient, and compressive strength of the samples were tested. The additives were 1, 2, 3, 4, 5, 7, and 9 wt% yttrium oxide. Figure 1 , 2 From the perspective of yttrium oxide, when the addition amount of yttrium oxide is in the range of 1-4wt%, the yttrium element exists in the liquid phase, and the high-temperature liquid phase can effectively promote particle rearrangement; when the addition amount of yttrium oxide is in the range of 5-9wt%, part of the yttrium element exists in the liquid phase, and part of it is pinned at the grain boundary in the form of yttrium silicate to inhibit grain growth, thereby promoting the density of ceramics. Increasing the density of ceramics will improve the mechanical properties of ceramics, but it will also increase the thermal expansion per unit volume, and the thermal expansion coefficient increases with the increase in the addition amount. The thermal shock resistance of ceramics is the result of the combined effect of mechanical properties and thermal expansion coefficient. Therefore, although the thermal expansion coefficient increases during the heating process, the ability of ceramics to withstand stress is also enhanced, and the thermal shock resistance of ceramics may be better. As can be seen from the table, when the addition amount of yttrium oxide is 5%, due to the formation of yttrium silicate crystals, tiny pores are generated inside the ceramic. The evenly distributed tiny pores can accommodate a part of the expansion. Therefore, even if the shrinkage rate of the sample with 5wt% added is larger than that of 4wt%, its water absorption rate increases slightly, the expansion coefficient decreases slightly, and the compressive strength increases significantly. Therefore, the addition amount of 5wt% is the best choice.
[0048] Table 1 Effect of yttrium oxide on ceramic properties
[0049]
[0050]
[0051] 2. Effect of aluminum titanate on ceramic properties
[0052] Ceramic samples were prepared according to the above method, and the true density, water absorption, sintering line shrinkage, thermal expansion coefficient, and compressive strength of the samples were tested. The additives were 2, 4, 6, and 8 wt% aluminum titanate. Figure 1 , 2From the perspective of the addition of aluminum titanate, the thermal expansion coefficient of ceramics can be significantly reduced, and some titanium ions in aluminum titanate still form a solid solution with the ceramic matrix, which promotes the densification of ceramics to a certain extent. However, since aluminum titanate is easy to decompose in the temperature range of 750℃-1300℃ and produce a phase with a large thermal expansion coefficient, and there will be a certain volume change during decomposition, a large number of microcracks will appear inside the ceramic sample. Too many cracks are easy to connect into large cracks, which significantly reduces the compressive strength of the ceramic sample.
[0053] Table 2 Effect of aluminum titanate on ceramic properties
[0054]
[0055] 3. Effect of yttrium oxide + aluminum titanate composite additives on ceramic properties
[0056] A large number of studies have shown that yttrium oxide has an inhibitory effect on the decomposition of aluminum titanate, but when the addition amount is relatively small, this inhibitory effect may not be obvious. At the same time, cordierite-mullite-corundum composite ceramics have certain restrictions on the sintering temperature, which cannot be too high, otherwise it will lead to the decomposition of cordierite. Therefore, this study carried out the following optimization to achieve the high density and low expansion characteristics of the composite ceramics.
[0057] (1) According to Study 1 "Effect of Yttrium Oxide on the Properties of Composite Ceramics", the amount of yttrium oxide added is 5% of the total mass of the ceramic;
[0058] (2) Based on Study 2 “Effect of aluminum titanate on ceramic properties”, the amount of aluminum titanate added was determined to be 6% of the total mass of the ceramic;
[0059] (3) Take 1 part of yttrium oxide and 6 parts of aluminum titanate by mass and mix them evenly - too much yttrium oxide may cause yttrium oxide to react with the aluminum element in aluminum titanate to form yttrium aluminum garnet, thereby promoting the decomposition of aluminum titanate;
[0060] (4) adding ultrapure water with a total weight of 15% of the additive; die-casting into blocks using a molding press; keeping the temperature at 1550° C. for 2 h and then cooling to room temperature; grinding and sieving to obtain a pre-sintered composite additive powder;
[0061] (5) Weighing ceramic raw materials by weight;
[0062] (6) taking 7% of the total mass of the ceramic raw material as pre-sintered composite additive powder, wherein 1% of the composite additive is yttrium oxide and 6% is aluminum titanate;
[0063] (7) adding 4% of yttrium oxide so that the sum of yttrium oxide and the yttrium oxide in the pre-sintered composite additive is 5%;
[0064] Ceramic samples were prepared according to the method described in Example 1; and the true density, water absorption, sintering line shrinkage, thermal expansion coefficient, and compressive strength of the samples were tested.
[0065] Table 3 Effect of pre-sintered composite additives on ceramic properties at different temperatures
[0066]
[0067] Comparative Example 1 A high-density honeycomb ceramic heat storage body, a high-density honeycomb ceramic heat storage body, is made of the following raw materials in parts by weight (kg): 50 parts of bauxite powder with an aluminum oxide content >80%, 3 parts of cordierite powder, 2 parts of Suzhou kaolin, 0.5 parts of pyrope powder, 25 parts of mullite powder, 3.5 parts of potassium feldspar, 4 parts of raw talc, 5% of the total mass of the powder by dispersant, 2% of the total mass of the powder by grinding aid, and 5wt% of the total mass of the powder by yttrium oxide.
[0068] The preparation method of honeycomb ceramics is as follows:
[0069] Weigh each raw material by weight, put the raw material into a ball mill, and ball-mill for 6 hours at a speed of 30 revolutions per minute to obtain a mixture; add the mixture into a kneader, add 2% of the mass of the mixture HPMC 100,000 viscosity cellulose, 2% of 28-degree palm oil, 8% of 5 million molecular weight polyethylene oxide, and 13% of deionized water, set the kneader speed to 30 revolutions per minute, knead for 20 minutes, and obtain a kneaded mud segment; put the kneaded mud segment into a vacuum mud kneading machine, and refine it at a vacuum degree of 0.07 to obtain a refined mud segment; use a mold to press it into a desired product to obtain a wet blank; dry the wet blank to obtain a dry blank; cut both ends of the dry blank, and the cutting size is 1-1.20 times the length of the finished product to obtain a cut dry blank; put the cut dry blank into a kiln, and sinter it at 1150°C to obtain a finished product.
[0070]
[0071] Comparative Example 2 is a high-density honeycomb ceramic heat storage body. The only difference between this example and Example 1 is that 6wt% of aluminum titanate is selected as the additive.
[0072]
[0073] Example 1 A high-density, low-expansion multiphase honeycomb ceramic thermal storage body. The only difference between this example and comparative example 1 is that the additive selected is 1% yttrium oxide + 6% aluminum titanate pre-sintered composite additive powder of the total powder mass plus 4% yttrium oxide powder of the total powder mass.
[0074]
[0075] The contents explained in the above embodiments should be understood as these embodiments are only used to more clearly illustrate the present invention, and are not used to limit the scope of the present invention. After reading the present invention, various equivalent forms of modifications to the embodiments made by those skilled in the art fall within the scope defined by the claims attached to the present invention.
Claims
1. A method for preparing a high-density, low-expansion composite honeycomb ceramic, characterized in that: A pre-sintered composite additive is added to the mixed ceramic raw material, the pre-sintered composite additive accounts for 5-9wt% of the weight of the mixed ceramic raw material, and the pre-sintered composite additive is prepared by mixing yttrium oxide and aluminum titanate in a mass ratio of 1:5-7, and pre-sintering and grinding at 1350-1600°C.
2. The method for preparing the high-density and low-expansion composite honeycomb ceramic according to claim 1, characterized in that: The pre-sintering temperature of the pre-sintered composite additive is 1500-1600°C.
3. The method for preparing the high-density and low-expansion composite honeycomb ceramic according to claim 1, characterized in that: The pre-sintering time of the pre-sintered composite additive is 1 to 3 hours.
4. The method for preparing the high-density and low-expansion composite honeycomb ceramic according to claim 1, characterized in that: 3-5wt% of yttrium oxide is also added to the mixed ceramic raw material.
5. The method for preparing the high-density and low-expansion composite honeycomb ceramic according to any one of claims 1 to 4, characterized in that: The sintering temperature of the high-density and low-expansion composite honeycomb ceramic is 1150°C-1400°C.
6. The method for preparing the high-density and low-expansion composite honeycomb ceramic according to claim 5, characterized in that: The sintering temperature of the high-density and low-expansion composite honeycomb ceramic is 1150°C-1350°C.
7. The method for preparing the high-density and low-expansion composite honeycomb ceramic according to any one of claims 1 to 4, characterized in that: The mixed ceramic raw material is a cordierite-mullite-corundum composite honeycomb ceramic raw material; preferably, the mixed ceramic raw material includes the following raw materials in parts by weight: 40-60 parts of bauxite powder with an aluminum oxide content >80%, 2-6 parts of cordierite powder, 1-4 parts of Suzhou kaolin, 0.5-1.5 parts of pyrope powder, 20-35 parts of mullite powder, 2-4 parts of potassium feldspar, 4-9 parts of raw talc, 2-5wt‰ of dispersant with a total powder mass, and 0.5-2wt‰ of grinding aid with a total powder mass.
8. The method for preparing the high-density and low-expansion composite honeycomb ceramic according to claim 7, characterized in that The following steps are involved: (1) Weighing each raw material by weight and ball-milling to obtain a mixed material; (2) adding cellulose, a lubricant, a plasticizer and water to the mixture and kneading to obtain a kneaded mud segment; (3) refining the kneaded mud segment to obtain a refined mud segment; (4) using a mold to press the refined mud segment into a desired product to obtain a wet blank; (5) drying the wet blank to obtain a dry blank; (6) cutting the two ends of the dry blank to obtain a cut dry blank; (7) The cut dry blank is fired to obtain a finished ceramic product.
9. A high-density, low-expansion multiphase honeycomb ceramic prepared according to the preparation method according to any one of claims 1 to 8.
10. A high-density, low-expansion composite honeycomb ceramic, characterized in that: The thermal expansion coefficient is less than 4.9×E-6, and the compressive strength is greater than 58MPa.
Citation Information
Patent Citations
Honeycomb heat accumulator made of silicon carbide-corundum composite materials
CN101798212B
Aluminum titanate-mullite-corundum saggers, their preparation methods and applications
CN108017387B
Multi-phase functional ceramic honeycomb support and preparation method thereof
CN101062868A
Ceramic materials for 4-way and nox adsorber and method for making same
CN103058650A
Aluminum titanate-mullite composite ceramic and preparation method thereof, porous medium combustor and ceramic filter
CN112723903A
Cited By
High-temperature-resistant special ceramic and preparation method thereof
CN121135385A